Strategic Planning Analysis of Grand Design of Population Development - Andjar Prasetyo; Dewi Gartika (Economics Development Analysis Journal, 2021)
The purpose of this study is to identify and analyze population data based on population structure and five population aspects, as well as regional areas in Kebumen Regency in 2020. Then prepare recommendations and plans to integrate population problems into development planning mechanisms and develop a 2020 Population Grand Design Model. The method of analysis used quantitative and qualitative descriptions with a locular in Kebumen Regency. The research was conducted using secondary data sources from the Central Bureau of Statistics of Kebumen Regency, the Department of Social Affairs and Population Control and Family Planning in Kebumen, the Ministry of Education and Culture. Primary data comes from the results of discussions with the Head of Service and structural officials at the Department of Social Affairs and Population Control and Family Planning in Kebumen, the results of the discussion become one of the qualitative indicators for analysis. The analysis was mainly carried out using SWOT and to complement the ARIMA method. The results are based on an administrative and substantive approach with the integration of five population aspects, namely Population Quantity Control, Population Quality Improvement, Population Mobility Direction, Family Development and Population Database Development, which are expected in the form of regional regulations.